Pengaruh Moral Perpajakan, Kekuasaan Otoritas Pajak, dan Persepsi Keadilan Perpajakan terhadap Tingkat Kepatuhan Wajib Pajak Kendaraan Bermotor dengan Religiusitas sebagai Variabel Pemoderasi (Studi Empiris pada Pemilik Kendaraan Bermotor yang Terdaftar di Kantor Bersama SAMSAT Kota Semarang I) - Eri Kartika; Hasan Mukhibad (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study aims to analyze the effect of tax morale, tax authority power, and perceptions of tax fairness on motor vehicle taxpayer compliance, with religiosity as a moderating variable. The study was conducted on motor vehicle taxpayers registered at the One- Stop Administration Office (SAMSAT) of Semarang City I. A quantitative approach with a survey design was employed. Primary data were collected through the distribution of Likert-scale questionnaires (1–5) to 100 respondents selected using a convenience sampling technique. The data were analyzed using the Structural Equation Modeling Partial Least Squares (SEM-PLS) method, which includes outer model testing, inner model testing, and hypothesis testing to examine direct effects and moderating effects among variables. The results indicate that tax morale, tax authority power comprising coercive power and legitimate power and perceptions of tax fairness have a positive and significant effect on motor vehicle taxpayer compliance. These findings suggest that taxpayer compliance is influenced by a combination of internal factors, such as moral values and individual perceptions, and external factors, including authority power and the enforcement of tax regulations. Furthermore, religiosity is proven to act as a moderating variable that strengthens the positive and significant effects of tax morale, tax authority power, and perceptions of tax fairness on motor vehicle taxpayer compliance. This result demonstrates that religious values enhance the internalization of moral attitudes, increase respect for authority, and strengthen taxpayers’ responses to the fairness of the tax system, thereby promoting more consistent and sustainable compliance.